Relasi Agama, Magi, Sains dengan Sistem Pengobatan Tradisional-Modern pada Masyarakat Pedesaan - Nasrudin, Juhana (Hanifiya: Jurnal Studi Agama-Agama, 2019)
This study examines the relation of Religion and the Traditional Medicine System to rural communities. The big conclusion of this dissertation shows that there are religious relations with the traditional medical system in the form of integration of religious functions into the traditional medicine system. Acculturation of religion and culture is evident in the traditional medicine system. The most important thing that characterizes traditional medicine is that at the practical level the traditional medical system in rural communities is inseparable from the magical and religious elements. So based on that religious function can be used as a function of therapy. This study uses qualitative methods, using two data sources. First, primary data obtained from document studies, field observations, In-depth Interview and Focus Group Discussion. The informant is obtained by Purposive and snowballing. Secondary data is supporting data obtained from books, journals, and magazines. To analyze the relationship between religion and the traditional medical system in rural communities, it was analyzed with three approaches to sociology, anthropology and psychology.